Development of a High BCAA Enkaje Ginger Mung Bean Enteral Formula For Cancer Patients - Amanda Bulan Ramadhani; Almas Dhiyani Lumintang; Dwi Sarbini (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The development of Enteral Formula with local food ingredients of mung bean flour produces enteral formulation from local food ingredients whose taste, aroma, color, and texture are acceptable to the community, and the osmolality value remains according to the standard to support the recovery of cancer patients. Objective: The purpose of this study was to develop a more economical Enteral Formula with a higher BCAA value than the Commercial Formula. Method: The type of research was quantitative with a Completely Randomized Design (CRD) experimental design. Result and Discussion: The results showed that F1, F2, F3, and Commercial were not readable with a viscometer, while the osmolality test of F2 476.5 mOsm/L, F3 450 mOsm/L and Commercial 400 mOsm/L obtained results according to the standard, while F1 was above the standard at 516 mOsm/L. The selected enteral formula was F2, with a ratio of 65% mung bean flour to 65% skim milk. The organoleptic test for taste, aroma, texture, and overall performance achieved the highest total of 60-79%, indicating a favorable and acceptable level of acceptance. Conclusion: It also had a lower price of Rp 4,868.17 per serving compared to the commercial formula at Rp 29,450. It also had a higher BCAA content than the commercial formula, in line with the research objectives